(untitled) (Research, Society and Development, 2021)
Objective: Discuss about the pilates method during pregnancy and its benefits for a natural birth. Methodology: This is a narrative bibliographic review, carried out through scientifically-based articles from journals available in electronic databases, such as google academico, scielo, books and magazines, researches that address the Pilates method in the gestational period that are in the years from 2011 to 2021. Key words that will be used for the research: pilates benefit, pregnancy, natural childbirth, pilates method. Results: The results that apply here, suggest that the practice of Pilates, during the gestational period, taking into account the dimensions that this exercise reaches, are, in short, determinants for the delivery process, as it meets the needs of expansion of the body, suggested to the organism. Final Considerations: Pilates presents in its frame a complex grid that meets the demands of the organism in a broad way, extending to punctual and ample pains.